Digital Marketing and Green Packaging Introduction Counseling to Increase the Competitiveness of Coffee Commodities at GAPOKTAN Mugi Lestari, Temanggung - Dhika Cahyasita; Herdiana Anggrasari; Dinda Dewi Aisyah (IJECS: Indonesian Journal of Empowerment and Community Services, 2025)
Coffee marketing by members of Gapoktan Mugi Lestari is currently still limited to offline, so it has a limited market share and is less well-known by the wider community. Coffee, as a commodity with high demand, has a wider market opportunity. This community service activity aims to increase the understanding of farmer group members about the importance of effective online marketing and introducing environmentally friendly packaging as an added value. The activity was carried out at Gapoktan Mugi Lestari, Temanggung, using lecture, discussion, and digital marketing practice methods using Shopee. The level of understanding and knowledge of members was evaluated through pre-tests and post-tests, which showed a significant increase from 63% to 85%, which was analyzed using the Paired Sample T-Test. The members' enthusiasm was very good because this activity could open up wider marketing opportunities and improve the household economy. In the future, the activity is expected to help with business licensing, assistance in standardizing coffee product quality, and managing certification, as well as training and counseling on digital marketing strategies. In addition, support is needed from the local government regarding the development of digital infrastructure in agricultural areas as well as digital literacy training, and the provision of subsidies or incentives for farmers who use environmentally friendly packaging. Keywords: Coffee UMKM, Digital Coffee Marketing, Eco-Friendly Packaging, Farmer Empowerment